Influencer marketing - Rodríguez Rodrigo, Juliana (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Studies show that surreptitious advertising is a common practice carried out by influencers. This behaviour is an attack on the followers and on the advertiser’s competitors. In relation to the former, because it is not clear about the commercial nature of the influencer’s message and may make them think that they are dealing with a personal opinion of their leader. Regarding the latter, because, with it, they are making the brand compete unfairly with the rest of the competitors in the market. It is important, therefore, to identify when the advertising carried out by influencers is illegal because it is covert. There are two elements that must be present in order to reach this conclusion. Firstly, there must be a commercial purpose, which can be proven by the existence of a remuneration. And, secondly, this promotional purpose of the influencer does not appear clear and unequivocal to the user. In relation to the latter, the follower cannot deduce this commercial character either from the content of the message or from its location and, on the other hand, the influencer has not incorporated the necessary information to make it known.